TINGKAT PENERAPAN HASIL PELATIHAN TEKNIS BUDIDAYA DAN KELAYAKAN USAHA PORANG - Widiyanto, Adi (Chlorophyl, 2022)
This research is an evaluation to determine the level of usefulness and application of training materials by training partisipants to subject matters that have been trained. This research uses descriptive method with quantitative approach and is supported by qualitative. Data collection by survey technique. The results of this study indicate that the level of material usefulness is in the range of useful levels. The level of application of the material for the overall training subject matters that has been trained on average is in the very high category. But there is material for Training Subject Matter Plant Care results of its application level not yet optimal, although still in high category. This is because control activities against pests and diseases of porang plants are not carried out because the attack rate is low. Porang is a plant with a low level of pest and disease attacks